HUBUNGAN USIA IBU DAN STATUS ANEMI DENGAN STATUS BERAT BAYI LAHIR PADA IBU HAMIL TRIMESTER III DI WILAYAH KERJA PUSKESMAS BANGETAYU KECAMATAN GENUK KOTA SEMARANG - Lisniawati, Anisa; Pertiwi, Estuasih Dyah (Poltekkes Kemenkes Semarang, 2015)
Background: The prevalence of anemia in pregnant women in Indonesia in 2013 was 37.1%. The prevalence of LBW in Central Java in 2013 was 9.7%. Whereas LBW in Bangetayu Health Center in 2013 and 2014 was 4.0%. The reproductive age is not optimal (age 20 years and 35 years) during pregnancy and the incidence of anemia in pregnant women is an important indicator of causes of LBW.Objective: . This research was conducted to find out the relationship between knowledge and attitudes of sanitation hygiene with the practice of sanitation hygiene in cooking food and biological quality in animal side dishes in Semarang City General Hospital.Methods: Research included in institutional nutrition with a crossectional approach. The research sample used was animal dishes made from chicken meat, the respondents who were used as the research were food cookers. The data taken includes knowledge, attitudes and practices on cooking staff and biological quality on animal dishes using questionnaires, observation and laboratory checks. To find out the relationship between variables tested with Rank Spearman and Pearson Product Moment.Results: Animal side samples 58.3% had good biological quality, 100% good sanitation hygiene knowledge, respondents sanitation hygiene attitude 66.7% did not support, respondents sanitation hygiene practices 50% good. There is no relationship between knowledge and attitudes with hygiene sanitation practices (p = 0.712 and p = 0.614). There is a significant relationship between the variables of hygiene sanitation practices and total bacteria (r = -0.706) with p = 0.01.Conclusion : Good sanitation hygiene practices will reduce total bacteria in food and will produce good biological quality. It is recommended to increase supervision of sanitation hygiene practices.